2012
DOI: 10.1136/thoraxjnl-2012-202093
|View full text |Cite
|
Sign up to set email alerts
|

The at-risk registers in severe asthma (ARRISA) study: a cluster-randomised controlled trial examining effectiveness and costs in primary care

Abstract: Background Patients at risk of severe exacerbations contribute disproportionally to asthma mortality, morbidity and costs. We evaluated the effectiveness and costs of using 'asthma risk registers' for these patients in primary care. Methods In a cluster-randomised trial, 29 primary care practices identified 911 at-risk asthma patients using British asthma guideline criteria (severe asthma plus adverse psychosocial characteristics). Intervention practices added electronic alerts to identified patients' records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 29 publications
(29 reference statements)
0
60
1
Order By: Relevance
“…4,12,13 This study contrasts with the findings of other research that reported decreased emergency admission with increasing distance from hospital and with higher deprivation. [31][32][33] The study differs from those in that a multilevel analysis was used clustering at the primary care trust level.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 56%
See 1 more Smart Citation
“…4,12,13 This study contrasts with the findings of other research that reported decreased emergency admission with increasing distance from hospital and with higher deprivation. [31][32][33] The study differs from those in that a multilevel analysis was used clustering at the primary care trust level.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 56%
“…4 Two English studies that targeted asthma patients at high risk of adverse outcomes by flagging the medical record and training staff to improve access have reported reduced hospital admission, as well as improved quality of care. 12,13 Increased emergency asthma admissions have been reported to be associated with decreased access to health care in North Carolina in the US.…”
mentioning
confidence: 99%
“…13,14 Most recently, the ARISSA study used "asthma risk registers" to help outpatient practices identify and focus on their highest-risk patients. 15 Many of these programs have seen positive outcomes, such as increased adherence to controller medications and more symptom-free days. However, few have significantly reduced asthma-related ED visits.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Few have significantly reduced ED utilization. This leads us to ask: are there reasons for asthma-related ED use that prior interventions have not addressed?…”
mentioning
confidence: 99%
“…There is proof of concept in adult populations that primary care records can be used to alert primary care staff to patients who are at high risk of asthma attacks,37 although differences in lifestyle (eg, smoking) and comorbidities (eg, COPD or diagnosed depression) mean that this needs to be replicated in children. “Avoiding hospital admissions”, a document by the King’ Fund, described an educational intervention to parent and child in accident and ED might reduce a child’s risk of future admissions by 20%;38 might this approach work in the primary care setting?…”
Section: Introductionmentioning
confidence: 99%